Introduction - Board, Editorial (Economy and Business Yearbook, 2022)
The seventh edition of the Economics and Business Yearbook of Department “Economics” at New Bulgarian University focuses on contemporary issues of the economy, business, finance, accounting and marketing. The published articles present the research activity of full–time faculty members and students from New Bulgarian University and colleagues from other universities. The main purpose of the publication is to make the research of tutors and students visible and accessible so that it could be used both as teaching materials in the Bachelors‘ and Masters‘ programs of the Department and the academia in general, as well as reference books for business. The scientific materials included are the results of thorough scientific and practical research conducted during the academic year 2021/2022. The articles in this year’s edition of the Economics and Business Yearbook present numerous theoretical and practical contributions in the fields of finance, marketing, management, accounting, EU policies, sustainable development, international trade, affecting current issues of the global, European and national economy. Their aim is to increase the efficiency and quality of training, to update the teaching material with the latest developments in the fields of economics and business, and together with this they bring to the attention of the academic community and business original and new views, analysis and solutions to important and topical issues of the global, the European and the Bulgarian economy.